Trois sonates pour le piano-forte : Oeuv. 2, No. 1 ... composées et dédiées à J. Haydn par L. van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Jean Aug. Böhme; Germany; Hamburg, 2022)
Edition of the Piano Sonata no. 1 in F minor, op. 2, no. 1, published in an unnamed series by Jean Aug. Böhme in Hamburg. With decorative passé-partout title page that lists individual and set prices for all three sonatas of op. 2. Plate number 1.